ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR KEDELAI DI INDONESIA TAHUN 1990-2021 - Untari, Wiwik Sri; Mayangsari, Andina; Fauzi, Farit Al (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The research objective was to determine the effect of production, consumption of harvested area and the exchange rate on Indonesian soybean imports. The data used in this study is secondary data in the form of time series data for the period 1990-2021. The research method used was Multiple Linear Regression with the help of SPSS version 25 software. The results showed that based on the results of multiple linear analysis, it was concluded that Indonesian soybean imports were significantly influenced by soybean production, soybean consumption, harvested area and the rupiah exchange rate against the dollar. Soybean production has a significant positive effect on soybean imports, while consumption has no significant effect. Harvested area and the rupiah-dollar exchange rate had a significant negative effect on soybean imports.